Determination of Antioxidants by DPPH Scavenging Activity of Ashitaba Herb (Angelica keiskei) Methanol Extract - Handa Muliasari; Nisa Isneni Hanifa; Wahida Hajrin; Mahacita Andanalusia; Agriana Rosmalina Hidayati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Ashitaba (Angelica keiskei) is one of the plants cultivated in the Sembalun region, Lombok, NTB, which has the potential to be developed as a source of antioxidants. This study aims to determine the antioxidant activity of the methanol extract of ashitaba herb by measuring the inhibition against DPPH (1,1-diphenyl-2-picrylhydrazyl) radicals using a UV-Vis spectrophotometer. Ashitaba herb samples were collected in Jorong Hamlet, Sembalun Bumbung Village, Sembalun District, East Lombok Regency at coordinates 8°23'5.273